PENERAPAN MODEL PEMBELAJARAN SAVI BERBANTUAN WORDWALL PADA PEMBELAJARAN IPA SEKOLAH DASAR - Pakaya, Pratiwi; Meylan Saleh; Rifda Mardian Arif; Abdul Haris Panai; Irvin Novita Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is a Classroom Action Research (CAR) with the formulation of the problem is whether the application of the SAVI learning model (Somatic, Auditory, Visual, Intellectual) assisted by Wordwall media can improve student learning outcomes in the subject of science on the material of changes in the state of matter in grade IV SDN 6 Tilongkabila. The purpose of this study is to improve student learning outcomes through the application of the SAVI learning model assisted by Wordwall media. This research was conducted in two cycles, where each cycle consisted of two meetings with four stages: planning, implementation of actions, observation, and reflection. The research subjects were 18 students consisting of 8 male students and 10 female students. The results of the study showed that in cycle I of 18 students only 4 students achieved the Learning Objective Achievement Criteria (KKTP ≥ 80) with a percentage of 22.2%, while 14 students or 77.78% had not achieved completeness. After improvements were made to the learning process in Cycle II, student learning outcomes significantly improved, with 17 students (94.44%) achieving mastery, while 1 student (5.56%) had not. Therefore, it can be concluded that the SAVI learning model, supported by Wordwall media, can improve student learning outcomes in the fourth-grade science subject of changes in state of matter at SDN 6 Tilongkabila.